“Notre voisine méconnue”: Margaret Laurence in Quebec - Drouin, Violette (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2024)
Though Margaret Laurence’s Manawaka Cycle was met with success upon its publication in English, it is no obvious feat to translate such success across the borders of language, even within her own home country. This article attempts to chart the complex history of the translation of the Manawaka Cycle into French and its reception in Quebec. Drawing on reviews, advertisements, letters, and the books themselves, it establishes two periods of translation, the first in the 1970s and 1980s, the second in the early 2000s. It traces the challenges faced by publishers of these translations, and how they adapted to the changing literary and political climate of the second half of the 20th century. It also touches on the complex relationship between French and French Canadian publishers. The article examines how Laurence’s work was received in Quebec and the space of translation in the collective literary memory. Finally, it compares translations and retranslations of two of Laurence’s novels to garner insight into the differences between the two periods of translation.